Circular Economy and Green Marketing: A Path Toward Zero-Waste Consumerism - Moorthy, Dr. D.; Akila, Dr. M.; Jeyadevi J, Dr. Christina (South Eastern European Journal of Public Health, 2025)
The growing urgency of addressing environmental challenges has propelled the concepts of circular economy and green marketing to the forefront of sustainable business strategies. This paper explores their synergistic potential in fostering zero-waste consumerism, emphasizing the shift from the traditional linear economic model of "take, make, dispose" to a regenerative framework that prioritizes resource efficiency, waste reduction, and sustainability. Circular economy principles advocate for designing out waste, keeping materials in use, and regenerating natural systems, while green marketing focuses on promoting environmentally friendly products and practices to align with consumer values. This study examines the integration of these concepts, highlighting successful strategies employed by businesses to minimize ecological footprints while maintaining profitability and consumer satisfaction. It delves into innovative practices such as eco-design, product lifecycle extension, and closed-loop supply chains, showcasing how green marketing can effectively communicate these efforts to environmentally conscious consumers. The paper also addresses key challenges, including regulatory barriers, consumer skepticism, and the trade-offs between environmental and economic goals. By analyzing case studies, current trends, and policy frameworks, this review identifies actionable insights for businesses aiming to adopt circular and green marketing practices. Ultimately, the findings underscore the transformative potential of these approaches in driving systemic change toward zero-waste consumerism. The integration of circular economy principles with effective green marketing not only enhances brand loyalty but also contributes to global sustainability goals. This review advocates for collaborative efforts among businesses, policymakers, and consumers to realize the vision of a zero-waste future, thereby fostering a sustainable and resilient economy.